Adam Smith and Rousseau ethics, politics, economics - Paganelli, Maria Pia 1972-; Rasmussen, Dennis C. 1978-; Smith, Craig 1977- (Edinburgh University Press, 2018)
This collection brings together an international and interdisciplinary group of Adam Smith and Jean-Jacques Rousseau scholars to explore the key shared concerns of these two great thinkers in politics, philosophy, economics, history and literature
Keywords: Smith, Adam / 1723-1790; Rousseau, Jean-Jacques / 1712-1778; Smith, Adam -- 1723-1790; Rousseau, Jean-Jacques -- 1712-1778; Political science / Philosophy; Philosophy, Modern / 18th century; Enlightenment; Ethics; Economics / Philosophy; Politik; Wirtschaft; Politische Ökonomie; Ethik; Konferenzschrift -- July 2015 -- Glasgow; Aufsatzsammlung